Ensino/aprendizagem musical no ensaio: um estudo de caso na Orquestra Camargo Guarnieri - Silva, Ruth de Sousa Ferreira (2012)
The aim of this research was to understand the process of both learning and teaching of music through the rehearsal of the Camargo Guarnieri Orchestra. It was also important to understand both the structure and organization of the rehearsals, the methods and both the individual and collective aspects applied in the learning and teaching processes during the rehearsals. A Case Study like this one, which applies the above focus, can contribute to the field of music education in the sense of helping the student to understand the process of production which is based on the knowledge of music, and the social context of such production. It also helps to understand the dynamics of both teaching and learning in this context in its social aspects and the various nuances of the process. The approach used for this research was one of a Case Study , which involved observation, written documents and various interviews with the Conductors in charge of the Orchestra. The reflections about the social relations in the group practices were based on Schutz (1970; 1964a; 1964b); as a social area on Bourdieu (2004), on Bozon (2000), about the musical hierarchies, and about music education knowledge on Kraemer (2000). In this context the aspects discussed were related to the institutionalization of the Orchestras, the musician s ability and the organizational dynamics of the rehearsals. Some of the conclusions of this Case Study are based on the different styles of the reaching/learning processes during the Orchestras rehearsals; rehearsals as an area/environment for teaching/learning music and; how the musicians rehearse, teach and learn with one another during the different stages of preparation of final piece.